Manajemen Sumber Daya Manusia Dalam Meningkatkan Kualitas Pendidikan - Sri Wahyuni Nasir; Makmur Syukri (Universitas Pahlawan Tuanku Tambusai, 2023)
Human resource management is recognized as very important by the head of the IT Darul Azhar Aceh Tenggara Private Middle School. The process of Human Resource Management in Improving the Quality of Education in Darul Azhar Aceh Tenggara IT Private Middle School is; (1). Doing good human resource planning, (2). Withdrawal of human resources (recruitment) for applicants who pass the requirements, (3). Selection by interview, (4) position placement according to performance, (5). Work appearance, (6). Conduct training and development to improve the ability of educators, (7). Compensation or allowances in the form of monthly salaries and allowances, (8). Work safety guarantee, (10). Effective continuing or retirement services and creating togetherness and openness to each other by not being suspicious of each other but trying to create a family working relationship. Keywords: Management, SDM, Education